2019
DOI: 10.1002/1348-9585.12050
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of lung cancer risk in indium-exposed workers: An 11-year multicenter cohort study

Abstract: Background We established a causal relationship between indium exposure and lung interstitial and emphysematous effects. Lung cancer has been clearly demonstrated in rats and mice exposed to indium phosphide and in rats exposed to indium tin oxide. However, no information is available on human indium‐related lung cancer. Methods The baseline studies were conducted on 381 indium‐exposed and 150 referent workers in 11 factories from 2003 to 2006. Items examined included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…This is in contrast to results from previous studies that reported an increased risk of lung cancer and interstitial pneumonia with indium exposure. In an 11-year cohort study (Nakano et al, 2019), the S-In and KL-6 levels were higher in indium-handling workers than in those who were not exposed. Other studies have also reported higher S-In, KL-6, and SP-D levels among indium-handling workers (Liu et al, 2012;Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is in contrast to results from previous studies that reported an increased risk of lung cancer and interstitial pneumonia with indium exposure. In an 11-year cohort study (Nakano et al, 2019), the S-In and KL-6 levels were higher in indium-handling workers than in those who were not exposed. Other studies have also reported higher S-In, KL-6, and SP-D levels among indium-handling workers (Liu et al, 2012;Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…The first case of interstitial pneumonia that was probably related to ITO inhalation was reported in 2003 (Homma et al, 2003). Indium compounds have subsequently been demonstrated to be associated with respiratory diseases such as interstitial pneumonia and lung cancer (Chonan, Taguchi & Omae, 2007;Hamaguchi et al, 2008;Cummings et al, 2010;Cummings et al, 2012;Omae et al, 2011;Nakano et al, 2014;Nakano et al, 2015;Nakano et al, 2019). Furthermore, they are related to emphysema, alveolar proteinosis and cholesterol granuloma (Chonan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, indium-exposed workers were also reported to have developed pneumoconiosis due to short-term exposure. 10,11 The early stages of pneumoconiosis are interstitial pneumonia, but this inflammation then disappears, while emphysema progresses according to time. Progressive emphysema depends on the concentration of indium in the blood.…”
Section: Progress In Educational Program For Diagnosis Of Occupationamentioning
confidence: 99%
“…A total of 1519 new cases of diagnosed from 2001 to 2015 as pneumoconiosis indicated that pneumoconiosis tended to be accelerated among young pneumoconiosis cases with shorter duration of exposure due to the high proportion of silicosis and the insufficient occupational health management in small and medium enterprises. In Japan, indium‐exposed workers were also reported to have developed pneumoconiosis due to short‐term exposure 10,11 . The early stages of pneumoconiosis are interstitial pneumonia, but this inflammation then disappears, while emphysema progresses according to time.…”
mentioning
confidence: 99%
“…The first case of interstitial pneumonia that was probably related to ITO inhalation was reported in 2003 (Homma et al, 2003). Indium compounds have subsequently been demonstrated to be associated with respiratory diseases such as interstitial pneumonia and lung cancer (Chonan, Taguchi & Omae, 2007;Hamaguchi et al, 2008;Cummings et al, 2010Cummings et al, , 2012Omae et al, 2011;Nakano et al, 2014Nakano et al, , 2015Nakano et al, , 2019. Furthermore, they are related to emphysema, alveolar proteinosis and cholesterol granuloma (Chonan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%